NONALCOHOLIC FATTY LIVER DISEASE AND RISK OF INCIDENT HYPERTENSION: A SYSTEMATIC REVIEW - Rossiyah, Nella (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
NAFL, or Non-Alcoholic Fatty liver, is a disorder characterized by the presence of steatosis; steatosis, an inflammation and expansion of liver cells with or without liver fibrosis (NASH, Non-Alcoholic Steatohepatosis); and cirrhosis. If more fibrosis or cirrhosis develops, the potential risk of liver cancer will grow. Current epidemiological research indicates that around 49.5% of people with hypertension also have NAFLD. In addition, the prevalence of hypertension is significantly higher in patients with NAFLD than in the general population. It has been proven that both the presence of NAFLD and the severity of the illness are significantly associated with higher risks of a broad spectrum of extrahepatic effects, including cardiovascular disease (CVD) and type 2 diabetes mellitus. Hypertension is a disorder characterized by multiple medical issues. In the majority of patients, the pathophysiological cause is unknown (essential or primary). Primary hypertension is incurable but can be managed. Another group with a low percentage has a unique cause, which is known as secondary hypertension. Endogenous and exogenous causes of secondary hypertension are numerous. If the source of secondary hypertension can be discovered, these patients' hypertension may be curable. All studies demonstrate that persons with NAFLD are more likely to have hypertension than those without NAFLD.